2020
DOI: 10.5811/westjem.2020.7.47796
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Emergency Department Social Risk and Social Needs

Abstract: Introduction: Social risks, or adverse social conditions associated with poor health, are prevalent in emergency department (ED) patients, but little is known about how the prevalence of social risk compares to a patient's reported social need, which incorporates patient preference for intervention. The goal of this study was to describe the relationship between social risk and social need, and identify factors associated with differential responses to social risk and social need questions. Methods: We conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 23 publications
2
25
0
Order By: Relevance
“…4,5 The emergency department (ED) is an ideal setting for examining the impact of SDoH on health outcomes and health service utilization. [6][7][8] Because ED patients are vastly diverse with regard to socioeconomic demographics and are likely to have higher rates of health-related social needs, EDs are particularly well-positioned to study and address social underpinnings of health inequities. Research has shown that reasons for using the ED as a primary access point for health care, even when insured, include challenges related to low socioeconomic status (eg, transportation, work release, and childcare for multiple visits), greater ability of EDs to meet patient time constraints (eg, single visit or "one-stop shop" service, 365/24/7 availability), and barriers to primary care (eg, difficulty keeping appointments, problems with after-hours coverage, scarcity of urgent appointments).…”
Section: Background and Significancementioning
confidence: 99%
“…4,5 The emergency department (ED) is an ideal setting for examining the impact of SDoH on health outcomes and health service utilization. [6][7][8] Because ED patients are vastly diverse with regard to socioeconomic demographics and are likely to have higher rates of health-related social needs, EDs are particularly well-positioned to study and address social underpinnings of health inequities. Research has shown that reasons for using the ED as a primary access point for health care, even when insured, include challenges related to low socioeconomic status (eg, transportation, work release, and childcare for multiple visits), greater ability of EDs to meet patient time constraints (eg, single visit or "one-stop shop" service, 365/24/7 availability), and barriers to primary care (eg, difficulty keeping appointments, problems with after-hours coverage, scarcity of urgent appointments).…”
Section: Background and Significancementioning
confidence: 99%
“…Urban ED patients comprise an at-risk, socially disadvantaged population, with elevated rates of unemployment, substance use, and mental health problems [33,34]. A recent ED-based study found that 37% of participants screened positively for social risks, defined as adverse social conditions associated with poor health, such as housing instability and food insecurity [35]. Additionally, compared to adults in the general household population, ED patients have an elevated prevalence of IPV.…”
Section: Study Goals and Significancementioning
confidence: 99%
“…[1][2][3][4] Recent scholarship in emergency medicine (EM) has turned to studying the upstream drivers of disenfranchised patients' reliance on ED services and the structural barriers to their overall health and well-being. [5][6][7][8] Similarly, EM educators have called for training structurally competent physicians-ones engaged in lifelong learning and self-reflection to recognize and respond to societal forces and structures that affect signs and symptoms of individual illness. 9 "Structural competency," first proposed by Metzl and Hansen, is defined as the trained ability for health professionals to recognize and respond to signs and symptoms of individual illness as the downstream effects of broad historical, social, political, and economic structures.…”
Section: Introductionmentioning
confidence: 99%